Online social networks : human cognitive constraints in Facebook and Twitter personal graphs /: human cognitive constraints in Facebook and Twitter personal graphs. (2015) - Arnaboldi, Valerio; Passarella, Andrea; Dunbar, R. I. M (Robin Ian MacDonald), 1947-; Conti, Marco, 1962-
No abstract available